2017
DOI: 10.1128/iai.01043-16
|View full text |Cite
|
Sign up to set email alerts
|

Peptoanaerobacter stomatis Primes Human Neutrophils and Induces Granule Exocytosis

Abstract: Peptoanaerobacter stomatis is a newly appreciated taxon associated with periodontal diseases; however, little is known about the organism's pathogenic potential or its interaction with the host immune response. Neutrophils are the most abundant innate immune cell present in the gingival tissue and function to constrain the oral microbial challenge. However, some periodontal pathogens have developed strategies to evade phagocytosis and killing by neutrophils. Therefore, to begin to understand the role of P. sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…3B). Recently our laboratory reported that another emerging periodontal pathogen, Peptoanaerobacter stomatis , is able to elicit a robust intracellular ROS production by human neutrophils (Jimenez Flores, Tian, Sizova, Epstein, Lamont, & Uriarte, 2017). Hence, we next examined if F. alocis could modulate the ROS production induced by P. stomatis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3B). Recently our laboratory reported that another emerging periodontal pathogen, Peptoanaerobacter stomatis , is able to elicit a robust intracellular ROS production by human neutrophils (Jimenez Flores, Tian, Sizova, Epstein, Lamont, & Uriarte, 2017). Hence, we next examined if F. alocis could modulate the ROS production induced by P. stomatis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another study compared the activation of the respiratory burst response when neutrophils were challenged with different periodontal pathogens; Fusobacterium nucleatum showed the highest intracellular and extracellular generation of ROS compared to P. gingivalis and Aggregatibacter actinomycetemcomitans (Katsuragi, Ohtake, Kurasawa, & Saito, 2003). Recently our laboratory showed that P. stomatis , an emerging oral pathogen, induces robust intracellular ROS production in human neutrophils, albeit the oxygen dependent response was not responsible for the antimicrobial activity (Jimenez Flores, Tian, Sizova, Epstein, Lamont, & Uriarte, 2017). In contrast, our results show that phagocytosis of F. alocis causes minimal intracellular and extracellular generation of reactive oxygen species; a phenotype, which to the best of our knowledge, is unique to F. alocis compared to other periodontal pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations